LIMK1 and LIMK2 regulate cortical development through affecting neural progenitor cell proliferation and migration - Rui Mao; Rui Deng; Yan Wei; Lifang Han; Yanghong Meng; Wei Xie; Zhengping Jia (Molecular Brain, 2019)
Abstract LIMK1 and LIMK2 are key downstream targets to mediate the effects of the Rho family small GTPases and p21-activated kinases (PAK) in the regulation of the actin cytoskeleton. LIMKs are also critical for synaptic transmission, plasticity and memory formation. Changes in LIMK signaling are associated with several neurodevelopmental and neurodegenerative diseases, including autism, intellectual disability and Alzheimer’s disease. However, the role of LIMK signaling in brain development remains unknown. In this study, we used LIMK1 KO and LIMK2 KO mice to investigate the role of LIMK signaling in the cerebral cortical development. We found that these KO mice are reduced in the number of pyramidal neurons in upper cortical layers and this reduction is accompanied by a smaller pool of neural progenitor cells and impaired neuronal migration. These results are similar to those found in PAK1 KO mice and suggest that LIMK-dependent actin regulation may play a key role in mediating the effects of PAK1 and Rho signaling in the regulation of cortical development.